The government manual for new superheroes - Brozik, Matthew David; Sager Weinstein, Jacob (Kansas City, Mo. : Andrews McMeel, 2005)
The Government Manual for New Superheroes is a hilarious, mock-official handbook that offers thorough, accessible, and completely zany advice for anyone who has always dreamed of donning a skintight spandex uniform and leaping across the rooftops of their cities. Going well beyond tights and capes, this manual provides insight into choosing a name, constructing a costume, choosing the right supertools of the supertrade, establishing a base of operations, maintaining a secret identity, taking or becoming a sidekick, joining a superheroic team, and even finding that special someone who gives meaning to a superhero's life-a nemesis. Extra features include a roster of superhero unions, a registration application, several useful charts and tips, and even a list of other government-sponsored periodicals for further reading. Destined to become a cult classic, The Government Manual for New Superheroes is an essential guide for every aspiring superhero.
Keywords: Heroes -- Humor